Godsdiens, evangelie en religie in die poësie met besondere verwysing na gedigte van Ida Gerhardt - Elst, J. van der (Koers, 1990)
It is characteristic of this famous poetess that she abhors evangelical poetry. She considers this kind of poetry often to be of poor quality, especially in the light of its explicit purpose to evangelize and convert readers to Christianity, h could be argued that the Dutch poetess Nel Benschop, of whom tens of thousands volumes of poetry are sold, writes such poetry. Despite her abhorrence of evangelical poetry, Gerhardt cannot summarily be regarded as an atheist artist. On the contrary, she may even be called a Christian poetess, but not in the dogmatic sense of the word. The impact of her work transcends the boundaries of Christianity. She often uses Christianity as a frame of reference along with Greek and Latin Classical references to give her poetry universality. To illustrate this I would like to compare her Easter poem ("Pasen") with some Easter poems of minor poets like Nel Benschop and l.L de Villiers. An analysis of the Easter poems shows that Gerhardt’s Easter poem obviously has a Christian framework but its implications are far wider.